Students' Illocutial Speech Acts in Indonesian Language Learning Activities in Class XI of SMA 3 Kota Serang - Hamdi Fadli (CV. ULIL ALBAB CORP, 2025)
This study aims to describe the types of students' illocutionary speech acts in Indonesian language learning in class, and the forms of students' illocutionary speech acts in Indonesian language learning in class. This study is a type of descriptive qualitative research and the data sources in this study are student speech with students and teacher speech with students in Indonesian language learning activities in class. The data collection technique for this study is the STLC (Listen Without Involvement). The results of this study found (10) utterances consisting of (3) directive speech acts, (3) expressive speech acts, (2) representative speech acts, (1) commissive speech acts, and (1) declarative speech acts.